Wacana dan Media; antara Kekuasaan, Representasi Ideologi dan Realita Sosial - Farida Maricar (Tekstual, 2018)
Media had a great influence and power toward daily activities. By media, we can understandourselves. It means our ability to speak and think, get in touch to other people, even our dreamand awareness of identity was formed by media. In other words, learning media was learningourselves as social creature. There were three views on discourse analysis. The first wasrepresented by empirical-positivism. The second was called constructivism konstruktivisme. Thethird was called as critical view. In understanding a discourse (texts), it could not be rid of thecontext. To find the reality behind the texts, it was necessary to investigate to the context of textproduction, text consumption and socio-cultural aspects which influence the text production .This was because a text was not rid of subjective interest. A text also needs meaning thatmeans a text already exist could be a picture on theories which will be used to analyze theproblem.